Analisis Sifat Mekanik Baja Karbon ST 37 Pada Variasi Kuat Arus dan Sudut Kampuh SMAW : Analisis Sifat Mekanik Baja Karbon ST 37 Pada Variasi Kuat Arus dan Sudut Kampuh SMAW - Sutrimo; Gugun Nugraha; Hanni Maksum Ardi; Toni Okviyanto; -, Dibyo Setiawan (Jurnal ELEMENTER (Elektro dan Mesin Terapan), 2023)
This study discusses the impact of variations in the seam angle of welded joints and welding parameters on the tensile strength and hardness testing of ST 37 carbon steel. The SMAW welding process is one of the metal connection techniques used in industry. The method of welding joints is carried out with variations in the seam angle of the welded joints 600 and 700, while variations in the current strength of the welded joints are 90A, 100A, and 110A. The experimental method used in this research is the steel base metal material ST 37, which has a thickness of 8 mm. The tensile strength test results have the highest value at the seam angle of 700 with a current strength of 110 A, namely 482.54 N/mm2. The lowest tensile strength test results were obtained with a tensile strength of 399.54 N/mm2 at a welded angle of 700 and a current strength of 90 A. The test specimen with a variation of the existing power of 110 A and a weld seam angle of 700 has the highest value in the hardness test with a 234 HV hardness.